Precocity of soybean cultivars on cultivation systems with corn in Areia, Paraíba State - DOI: 10.4025/actasciagron.v31i3.675 - Viana, Jeandson Silva (2009)
The objective of this work was to evaluate the effect of cultivation systems, associated or not with an inoculant, in the precocity of soybean cultivars at the green grain growth stage. The research was led in field conditions, in CCA/UFPB, Areia-PB with an experimental design in randomized blocks, in sub-subdivided plots (3 x 2 x 2), three cultivars (Pati, JLM 004 and Pirarara), with and without inoculation and in systems of single cultivation and intercropped with corn, with four replicates. Cultivar precocity was evaluated through the numbers of days until emergence, flowering, and maturation, the reproductive period and the number of harvested plants. The cultivar JLM 004 features the longest emergence period, but it develops to the other reproductive phases in less time and with lower number of plants at harvest; cultivar Pirarara presents the longest time for the reproductive cycle, the same as cultivar Pati, when intercropped and with inoculation; the intercrop system and the inoculation increase the number of days for the maturation of cultivar Pati, while the monocrop system and without inoculation extends the necessary time for the maturation of cultivar Pirarara.